Feasibility of a Nurse-Led Weekend Group Exercise Program for People after Stroke. (24th January 2017) - Scrivener, Katharine; Tourany, Raymond; McNamara-Holmes, Mary; Schurr, Karl; Dorsch, Simone; Dean, Catherine
Abstract : Background. Additional physical activity including repetitive task practice can improve outcomes after stroke. The additional practice can be facilitated by therapists and family members or could also be delivered by nursing staff. Objective. To investigate the feasibility of a nurse-led weekend exercise program after stroke. Participants. Individuals after stroke, who participated in a weekend exercise program during their hospital admission. Methods. A retrospective audit of the number of referrals to and amount of exercise repetitions achieved in a nurse-led weekend exercise program was undertaken. The weekend exercise program occurs on each Saturday and Sunday for one hour. The repetitions of exercise completed during each class were documented by staff. An audit was conducted to ascertain the amount and type of exercise completed within the class. Results. During the study period 284 people were referred to the exercise program. The mean number of exercise repetitions completed per participant in each class was 180.7 (SD 205.4). The number of exercise repetitions completed by participants was highly variable ranging from 0 to 1190 per class. Conclusion. The amount of average exercise repetitions completed in the Weekend Warrior program was large but with significant variability. A nurse-led exercise class is a feasible method of delivering exercise opportunities to individuals in hospital after stroke.